Effects of N-acetyl cysteine on serum podocalyxin and pentraxin levels in an experimental lower extremity ischemia-reperfusion injury model - Karakeci, Emel Sabaz; Gurbuz, Mustafa Limit (Univ Zulia, Facultad Ciencias Veterinarias, 2026)
Ischemia-reper fusion injury causes oxidative stress and inflammation, leading to skeletal muscle damage. This study investigates the role of N-acetylcysteine in modulating oxidative stress and inflammatory biomarkers specifically Podocalyxin and Pentraxin 3 in a rat model of lower extremity Ischemia-reperfusion injury. An experimental, controlled animal study conducted at the Experimental Research Center of Firat University. Twenty-four female Sprague-Dawley rats were allocated into four groups: control, sham, Ischemia-reperfusion, and Ischemia-reperfusion treated with N-acetylcysteine. Ischemia was induced by clamping the infrarenal abdominal aorta for 120 min, followed by 120 min of reperfusion. A single dose of N-acetylcysteine (150 mgkg-1, i.p.) was administered at the onset of reperfusion in the treatment group. Levels of serum Total Oxidative Status and Total Antioxidant Status, as well as the expression of Podocalyxin and Pentraxin 3 in tissue, were evaluated. A significant increase in Oxidative Status levels and a significant decrease in Antioxidant Status levels were observed in the Ischemia-reperfusion group compared to the control group. After administering N-acetylcysteine, there was a significant decrease in Oxidative Status levels and a significant increase in Antioxidant Status levels when compared to the Ischemia-reperfusion group. Histological evaluation showed that N-acetylcysteine reduced edema, hemorrhage, and overall tissue injury scores. Immunohistochemical analyses revealed increased Podocalyxin and Pentraxin 3 expression in Ischemia-reperfusion group tissues, which was notably diminished in the N-acetylcysteine-treated group. N-acetylcysteine demonstrated protective effects against Ischemia-reperfusion-induced oxidative and inflammatory damage in skeletal muscle by reducing serum and tissue levels of Podocalyxin and Pentraxin 3. These findings suggest its therapeutic potential in mitigating Ischemia-reperfusion injury and highlight Podocalyxin and Pentraxin 3 as promising biomarkers for tissue damage and treatment monitoring.
Keywords: Ischemia-Reperfusion Injury; N-Acetylcysteine; Podocalyxin; Pentraxin 3; Oxidative Stress; Skeletal Muscle